The neuroprotective effect of a traditional herbal (kyung‐ok‐ko) on transient middle cerebral artery occlusion‐Induced ischemic rat brain. Issue 2 (June 2015) - Park, Sang-In; Lee, Jin‐Hee; Chung, Yong‐An; Park, Moon‐Seo; Sunwoo, Hyun; Lee, Kwan‐Sung; Sunwoo, Yun‐Young
ABSTRACT Kyung‐ok‐ko (KOK) has been used for the treatment of central nervous system disorders such as amnesia, dementia, and cerebral ischemia. However, the effects of KOK on transient ischemic‐induced neuronal damage are still unclear. We examined whether KOK improves functional recovery and has a neuroprotective effect on infarction volume after transient middle cerebral artery occlusion (MCAO). KOK (50, 100, and 200 mg/kg) was administered orally following reperfusion and twice per day for 14 days post‐MCAO. Infarction volume was measured using 2% 2‐3‐5 triphenylterazolium (TTC) staining at 14 days post‐MCAO and alteration in regional cerebral blood flow (rCBF) after KOK treatment was monitored. Functional improvement was evaluated using adhesive removal and treadmill tests at 1, 7, and 14 days post‐MCAO. Also, apoptotic cell death was assessed by terminal deoxynucleotidyl‐transferase mediated d‐UTP‐biotin nick end (TUNEL) in the peri‐infarction region. The protein level of inflammatory cytokines such as tumor necrosis factor‐α (TNF‐α), interleukin‐1α (IL‐1α), and interleukin‐1β (IL‐1β) was measured in the ischemic core, ischemic border zone, and contralateral hemisphere regions. The KOK‐treated group showed both reduced infarction volume and behavior tests demonstrated a significant improvement as compared to the control. Also, in the KOK‐treated group, rCBF was recovered to near normal levels. The apoptotic cells were significantly decreased as compared with the control group in the ischemic peri‐infarction area. Furthermore, the level of TNF‐α, IL‐1β, and IL‐1α was decreased. These results suggest that KOK may improve functional outcome by inhibiting inflammatory cytokines (TNF‐α, IL‐1β, and IL‐1α) in neuronal injury such as ischemic stroke.